Photonic Liquid Crystal Fibers – 15 years of research activities at Warsaw University of Technology - Woliński, Tomasz; Ertman, Sławomir; Rutkowska, Katarzyna; Budaszewski, Daniel; Sala-Tefelska, Marzena; Chychłowski, Miłosz; Orzechowski, Kamil; Bednarska, Karolina; Lesiak, Piotr (Photonics Letters of Poland, 2019)
Research activities in the area of photonic liquid crystal fibers carried out over the last 15 years at Warsaw University of Technology (WUT) have been reviewed and current research directions that include metallic nanoparticles doping to enhance electro-optical properties of the photonic liquid crystal fibers are presented. Full Text: PDF References T.R. Woliński et al., "Propagation effects in a photonic crystal fiber filled with a low-birefringence liquid crystal", Proc. SPIE, 5518, 232-237 (2004). CrossRef F. Du, Y-Q. Lu, S.-T. Wu, "Electrically tunable liquid-crystal photonic crystal fiber", Appl. Phys. Lett. 85, 2181-2183 (2004). CrossRef T.T. Larsen, A. Bjraklev, D.S. Hermann, J. Broeng, "Optical devices based on liquid crystal photonic bandgap fibres", Opt. Express, 11, 20, 2589-2596 (2003). CrossRef T.R. Woliński et al., "Tunable properties of light propagation in photonic liquid crystal fibers", Opto-Electron. Rev. 13, 2, 59-64 (2005). CrossRef M. Chychłowski, S. Ertman, T.R. Woliński, "Splay orientation in a capillary", Phot. Lett. Pol. 2, 1, 31-33 (2010). CrossRef T.R. Woliński et al., "Photonic liquid crystal fibers — a new challenge for fiber optics and liquid crystals photonics", Opto-Electron. Rev. 14, 4, 329-334 (2006). CrossRef T.R. Woliński et al., "Influence of temperature and electrical fields on propagation properties of photonic liquid-crystal fibres", Meas. Sci. Technol. 17, 985-991 (2006). CrossRef T.R. Woliński et al., "Photonic Liquid Crystal Fibers for Sensing Applications", IEEE Trans. Inst. Meas. 57, 8, 1796-1802 (2008). CrossRef T.R. Woliński, et al., "Multi-Parameter Sensing Based on Photonic Liquid Crystal Fibers", Mol. Cryst. Liq. Cryst. 502: 220-234., (2009). CrossRef T.R. Woliński, Xiao G and Bock WJ Photonics sensing: principle and applications for safety and security monitoring, (New Jersey, Wiley, 147-181, 2012). CrossRef T.R. Woliński et al., "Propagation effects in a polymer-based photonic liquid crystal fiber", Appl. Phys. A 115, 2, 569-574 (2014). CrossRef S. Ertman et al., "Optofluidic Photonic Crystal Fiber-Based Sensors", J. Lightwave Technol., 35, 16, 3399-3405 (2017). CrossRef S. Ertman et al., "Recent Progress in Liquid-Crystal Optical Fibers and Their Applications in Photonics", J. Lightwave Technol., 37, 11, 2516-2526 (2019). CrossRef M.M. Tefelska et al., "Electric Field Sensing With Photonic Liquid Crystal Fibers Based on Micro-Electrodes Systems", J. Lightwave Technol., 33, 2, 2405-2411, (2015). CrossRef S. Ertman et al., "Index Guiding Photonic Liquid Crystal Fibers for Practical Applications", J. Lightwave Technol., 30, 8, 1208-1214 (2012). CrossRef K. Mileńko, S. Ertman, T. R. Woliński, "Numerical analysis of birefringence tuning in high index microstructured fiber selectively filled with liquid crystal", Proc. SPIE - The International Society for Optical Engineering, 8794 (2013). CrossRef O. Jaworska and S. Ertman, "Photonic bandgaps in selectively filled photonic crystal fibers", Phot. Lett. Pol., 9, 3, 79-81 (2017). CrossRef I.C. Khoo, S.T.Wu, "Optics and Nonlinear Optics of Liquid Crystals", World Scientific (1993). CrossRef P. Lesiak et al., "Thermal optical nonlinearity in photonic crystal fibers filled with nematic liquid crystals doped with gold nanoparticles", Proc. SPIE 10228, 102280N (2017). CrossRef K. Rutkowska, T. Woliński, "Modeling of light propagation in photonic liquid crystal fibers", Photon. Lett. Poland 2, 3, 107 (2010). CrossRef K. Rutkowska, L-W. Wei, "Assessment on the applicability of finite difference methods to model light propagation in photonic liquid crystal fibers", Photon. Lett. Poland 4, 4, 161 (2012). CrossRef K. Rutkowska, U. Laudyn, P. Jung, "Nonlinear discrete light propagation in photonic liquid crystal fibers", Photon. Lett. Poland 5, 1, 17 (2013). CrossRef M. Murek, K. Rutkowska, "Two laser beams interaction in photonic crystal fibers infiltrated with highly nonlinear materials", Photon. Lett. Poland 6, 2, 74 (2014). CrossRef M.M. Tefelska et al., "Photonic Band Gap Fibers with Novel Chiral Nematic and Low-Birefringence Nematic Liquid Crystals", Mol. Cryst. Liq. Cryst., 558, 184-193, (2012). CrossRef M.M. Tefelska et al., "Propagation Effects in Photonic Liquid Crystal Fibers with a Complex Structure", Acta Phys. Pol. A, 118, 1259-1261 (2010). CrossRef K. Orzechowski et al., "Polarization properties of cubic blue phases of a cholesteric liquid crystal", Opt. Mater. 69, 259-264 (2017). CrossRef H. Yoshida et al., "Heavy meson spectroscopy under strong magnetic field", Phys. Rev. E 94, 042703 (2016). CrossRef J. Yan et al., "Extended Kerr effect of polymer-stabilized blue-phase liquid crystals", Appl. Phys. Lett. 96, 071105 (2010). CrossRef C.-W. Chen et al., "Random lasing in blue phase liquid crystals", Opt. Express 20, 23978-23984 (2012). CrossRef C.-H. Lee et al., "Polarization-independent bistable light valve in blue phase liquid crystal filled photonic crystal fiber", Appl. Opt. 52, 4849-4853 (2013). CrossRef D. Poudereux et al., "Infiltration of a photonic crystal fiber with cholesteric liquid crystal and blue phase", Proc. SPIE 9290 (2014). CrossRef K. Orzechowski et al., "Optical properties of cubic blue phase liquid crystal in photonic microstructures", Opt. Express 27, 10, 14270-14282 (2019). CrossRef M. Wahle, J. Ebel, D. Wilkes, H.S. Kitzerow, "Asymmetric band gap shift in electrically addressed blue phase photonic crystal fibers", Opt. Express 24, 20, 22718-22729 (2016). CrossRef K. Orzechowski et al., "Investigation of the Kerr effect in a blue phase liquid crystal using a wedge-cell technique", Phot. Lett. Pol. 9, 2, 54-56 (2017). CrossRef M.M. Sala-Tefelska et al., "Influence of cylindrical geometry and alignment layers on the growth process and selective reflection of blue phase domains", Opt. Mater. 75, 211-215 (2018). CrossRef M.M. Sala-Tefelska et al., "The influence of orienting layers on blue phase liquid crystals in rectangular geometries", Phot. Lett. Pol. 10, 4, 100-102 (2018). CrossRef P. G. de Gennes JP. The Physics of Liquid Crystals. (Oxford University Press 1995). CrossRef L.M. Blinov and V.G. Chigrinov, Electrooptic Effects in Liquid Crystal Materials (New York, NY: Springer New York 1994). CrossRef D. Budaszewski, A.J. Srivastava, V.G. Chigrinov, T.R. Woliński, "Electro-optical properties of photo-aligned photonic ferroelectric liquid crystal fibres", Liq. Cryst., 46 2, 272-280 (2019). CrossRef V. G. Chigrinov, V. M. Kozenkov, H-S. Kwok. Photoalignment of Liquid Crystalline Materials (Chichester, UK: John Wiley & Sons, Ltd 2008). CrossRef M. Schadt et al., "Surface-Induced Parallel Alignment of Liquid Crystals by Linearly Polymerized Photopolymers", Jpn. J. Appl. Phys.31, 2155-2164 (1992). CrossRef D. Budaszewski et al., "Photo-aligned ferroelectric liquid crystals in microchannels", Opt. Lett. 39, 4679 (2014). CrossRef D. Budaszewski, et al., "Photo‐aligned photonic ferroelectric liquid crystal fibers", J. Soc. Inf. Disp. 23, 196-201 (2015). CrossRef O. Stamatoiu, J. Mirzaei, X. Feng, T. Hegmann, "Nanoparticles in Liquid Crystals and Liquid Crystalline Nanoparticles", Top Curr Chem 318, 331-392 (2012). CrossRef A. Siarkowska et al., "Titanium nanoparticles doping of 5CB infiltrated microstructured optical fibers", Photonics Lett. Pol. 8 1, 29-31 (2016). CrossRef A. Siarkowska et al., "Thermo- and electro-optical properties of photonic liquid crystal fibers doped with gold nanoparticles", Beilstein J. Nanotechnol. 8, 2790-2801 (2017). CrossRef D. Budaszewski et al., "Nanoparticles-enhanced photonic liquid crystal fibers", J. Mol. Liq. 267, 271-278 (2018). CrossRef D. Budaszewski et al., "Enhanced efficiency of electric field tunability in photonic liquid crystal fibers doped with gold nanoparticles", Opt. Exp. 27, 10, 14260-14269 (2019). CrossRef